Modified creatine greatly increases the performance of skeletal and smooth muscles - Soloviev, Anatoly; Kozlovsky, Vadym; Nozdrenko, Dmytro; Sydorenko, Vadym; Monchak, Igor; Vdovenko, Natalia; Maidaniuk, Olena; Fetyukhin, Volodymyr (Biochemistry and biophysics reports, 2025)
Creatine is a nitrogen-containing carboxylic acid and a main component of phosphocreatine. In recent years, creatine is considered as a component of dietary nutrition, to improve the efficiency of physical activity and increase muscle mass of athletes and older people. Creatine has been shown to be able restore cardiac contractility impairment after myocardial infarction. However, as muscle cells do not synthesise creatine, the efficiency of creatine depends on its transmembrane transport. In our study, we evaluated the effect of «ProCreatine» (ProCr), a novel membrane transporter-independent creatine modification on fatigability of the rat gastrocnemius muscle and portal vein smooth muscle using fatigue stimulation pools. Mechanokinetic and biomechanical markers of fatigue in muscles to maintain the level of isometric tension induced by field electrical stimulation were examined. The results indicate that administration of ProCr to skeletal muscle significantly increases maximal force output, integrated muscle contractile force and significantly increases muscle productivity. We observed positive changes in all studied biochemical indices of fatigue. In addition, ProCr increases the duration of sustaining a constant level of isometric contraction in portal vein smooth muscle caused by electrical stimulation by 6 fold. Regular creatine in the same dose had no significant effect on these parameters neither in skeletal nor in smooth muscles. The data obtained suggest the possibility of using ProCr as a therapeutic agent capable of reducing and correcting pathological conditions of the muscular system that arise during the processes of fatigue in skeletal muscles and smooth muscles of hollow organs.
Keywords: Creatine phosphokinase; Fatigue; Portal vein; Skeletal muscle; Creatine; Lactate